Percursos formativos do professor de educação infantil - Torres, Berenice de Souza (2020)
The research was carried out in the research line “New Technologies in Education”, of the Postgraduate Program in Education: Curriculum, of the Pontifícia Universidade Católica, in São Paulo. It aims to analyze the process of building the professional identity of the teacher at the Child Education Centers (CEI), of the Municipal Education Secretariat of São Paulo, State of São Paulo. It seeks to articulate the implementation of public educational policies, teacher training and early childhood education. To achieve this goal, a qualitative research was carried out, investigating 21 early childhood teachers through the collection of data on the academic and professional trajectory of teachers in office in 2019. The results show a sample of how these teachers arrived to work with early childhood education. The reflection and analysis of quantitative data highlights the academic and professional trajectory of teachers of early childhood education at the Municipal Department of Education of São Paulo. Based on questionnaires carried out in a CEI in the center of São Paulo, questions were raised that help to understand the construction of the teacher of early childhood education. Here is a profile of these professionals and their engagement with their work, despite the challenges and with constant training, whether through documentation, the prescribed curriculum or other study spaces